Human anti-IgM iso-antibodies in subjects with selective IgA deficiency - Wells, J. Vivian (1972)
IgG-class iso-antibodies against human IgM (`reverse rheumatoid factors') were detected in titres from 1:4 to 1:1024 in the serum of twelve of forty subjects (30%) with selective IgA deficiency. The antibodies were detected in a haemagglutination system with red cells coated by the chromic chloride method with proteins from a panel including nineteen Waldenström macroglobulins. The forty subjects included seventeen normal subjects, ten with recurrent infections, seven with ataxia telangiectasia, two each with asthma and lymphoma and one each with rheumatoid arthritis and chronic active hepatitis. Four of the twelve positive sera contained `class-specific anti-IgM' which reacted with all or most of the IgM coats. The eight sera containing `anti-IgM of limited specificity' included six reacting with only one IgM coat, one reacting with two IgM coats and one reacting with four IgM coats. The anti-IgM in the latter serum defined an inherited allotypic marker on these four IgM proteins. There was no significant correlation between the presence of anti-IgM antibodies and the clinical status, sex and age of the patient nor the presence of antibodies against human IgG, human IgA and ruminant proteins. These antibodies against human IgM represent yet another immunologic abnormality in this group of patients.